An indole alkaloid produced by Indonesian's marine sponge Raspailia ramosa as an inhibitory of the panc-1 cell adapted to nutrient starvation. (December 2018) - Kurnianda, V; Ramadhan, M R; Karina, S; Agustina, S; Ulfah, M; Octavina, C; Mardiah, A; Syahliza, F; Purnawan, S
Abstract: The bioactivity from Indonesian's Marine Sponge Raspailia ramosa has been done on July 2018. Bioactive compound isolated based on bioassay-guided separation with several steps of chromatography. The active metabolite compound of Raspailia ramosa has cytotoxic activity against PANC-1 cell with IC50 = 10 µg / mL. Based on NMR spectrum shows that the active compound has molecular formula C16 H17 N4 Br determined by LCMS-ESI with molecular weight [M+H] + 345.23 m/z. The FTIR spectrum shows that metabolic metabolites have NH secondary amines 3435.56 cm-1 with CN imine fingerprint area (1637.27 cm-1), CH methyl (2853.39 cm-1), CH methylene (2769.64 cm-1) indicate as indole alkaloid. The active metabolite compound of Raspailia ramosa has cytotoxic activity against PANC-1 cellwithIC50 = 10 µg / mL. This compound has the potential activity for the drug model for commercial drug antimycin = 0.1 μg / mL.